Hepatitis E infection among Ghanaians: a systematic review - Ofori-Asenso, Richard (Infect Dis Poverty, 2017)
BACKGROUND: Hepatitis E virus (HEV) infection is considered to be of significant public health importance in many developing countries. In this review, we aim to summarise studies on HEV with the aim of providing a further understanding of the epidemiology of the disease in Ghana. METHODS: A systematic review was conducted by following the recommendations outlined in the PRISMA statement. Studies on HEV infection among Ghanaians were identified by searching for articles (published up until 4th August 2016) in the PubMed, ISI Web of Science, African Journals Online, Google Scholar and the WHO African Index Medicus databases. We also searched the websites of the Ministry of Health and the Ghana Health Service to identify any related non-indexed studies. References of all retrieved studies were screened to identify additional publications. RESULTS: Ten studies involving a total of 2 894 participants from six regions of Ghana were identified. The proportion of Ghanaians showing positive serological markers for HEV infection was within the range of 5.8–71.55%. In addition, 0.7–45.9% tested positive for IgM antibodies while the proportion of Ghanaians testing positive for IgG antibodies was within the range of 0–45.3%. One study reporting a case fatality rate of 66.7% among pregnant women was identified. No information on HEV genotypes was retrieved. CONCLUSIONS: Although based on a limited number of studies, this review does highlight that there is a high level of HEV infection among Ghanaians. Preventive measures including educational interventions as well as general improvements to sanitary and living conditions are needed to reduce the burden of the disease. Additionally, further research regarding the contribution of the various HEV genotypes is urgently needed to fully understand the burden of this disease in Ghana. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s40249-017-0239-9) contains supplementary material, which is available to authorized users.